Nuclear Education in Russia and Abroad - Yu. N. Volkov; N. I. Geraskin; A. N. Kosilov (Высшее образование в России)
The education of a future nuclear professional provides the basic competencies that will influence the performance of a future specialist throughout his or her future professional career. The article discusses the best practices and main trends in higher education that have developed in the field of nuclear technologies in Russia and abroad. The analysis is based on the materials prepared by various international organizations and professional communities, and the experience of the MEPhI. The article discusses such issues as interaction between state, nuclear industry and higher education institution; the quality of nuclear education (four basic principles of training nuclear specialists in MEPhI), the transition to two-tier system in nuclear education; the international cooperation in nuclear sphere; export of nuclear education; and vocational guidance for school students.